ANALISIS PENGEMBANGAN WISATA HALAL DALAM PROSPEK MEMBANTU MENINGKATKAN PEREKONOMIAN DI INDONESIA - Devitasari Devitasari; Muhammad Iqbal Fasa; Soeharto Soeharto (LP2M Universitas Bina Bangsa, 2022)
This study discusses the development of halal tourism in order to improve the economy in Indonesia. The tourism sector is Indonesia's pillar to earn foreign exchange. Tourism can be used as an engine of economic growth for the country. Tourism is an economic activity that cannot be separated from behavior and economic actors, in which there are community actors as consumers, companies as service providers, and the state as a regulator. Islamic economics considers all economic activities inseparable from the three pillars of the Islamic economic concept in the form of property ownership, management and utilization of property, and distribution of property. Therefore, the concept of halal tourism should discuss all aspects with the approach of the three pillars of Islamic economics, in order to get a comprehensive view of halal tourism in terms of the principles of the owner of the goods and services being managed, the management model, the implementer of its management, and the distribution system in the community